2021
DOI: 10.1371/journal.pone.0256236
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and associated factors among people with epilepsy and attending outpatient treatment at primary public hospitals in northwest Ethiopia: A multicenter cross-sectional study

Abstract: Objective To assess the magnitude and factors associated with depression and anxiety among people with epilepsy and attending out-patient treatment at central Gondar zone primary public hospitals, northwest, Ethiopia. Method An institutional based cross-sectional study was conducted from May—June, 2020 at central Gondar zone primary public hospitals. A total of 589 participants were chosen by systematic sampling technique. Data was collected by utilizing Amharic version interviewer-administered structured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…In general, high-risk and frequent exacerbation patients need to change medication or polypharmacy, which often causes adverse effects both physical and psychological ( 38 , 39 ). Moreover, patients with polypharmacy are not only prone to psychological comorbidities such as anxiety and depression ( 40 ), but also increase the risk of drug interactions and long-term drug toxicity ( 41 ). Compared to healthy people, epilepsy patients require long-term AEDs treatment in combination with other drugs, resulting in higher economic and physical burdens ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, high-risk and frequent exacerbation patients need to change medication or polypharmacy, which often causes adverse effects both physical and psychological ( 38 , 39 ). Moreover, patients with polypharmacy are not only prone to psychological comorbidities such as anxiety and depression ( 40 ), but also increase the risk of drug interactions and long-term drug toxicity ( 41 ). Compared to healthy people, epilepsy patients require long-term AEDs treatment in combination with other drugs, resulting in higher economic and physical burdens ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is observed variability in the prevalence of these mental disorders among PWE across the world [ 9 ]. For example, a high prevalence of depression and anxiety was reported in the United Arab Emirates (26.9% and 25.8%), China (52.6% and 33.4%), Brazil (24.4% and 39.4%), Thailand (20% and 39%), Iran (9.5% and 24.5%), USA (26.9% and 25.8%), and Canada (17.4% and 22.8%) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PWE experience various difficulties that may trigger emotional burdens, such as loss of control in life due to unexpected seizures, diminished disease adaptation, and limited quality of life [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 5 million people in Sub-Saharan Africa have epilepsy [1]. One third of people living with epilepsy (PLWE) in Sub-Saharan Africa experience depression [2], and over one third experience anxiety [3]; in comparison, the estimated prevalence in PLWE overall is 9%-37% for depression and 11%-25% for anxiety [4]. Cross-sectional studies from multiple Sub-Saharan African countries have shown that the prevalence of depressive symptoms is high in PLWE, ranging from 40% (Ethiopia) to 86% (East Nigeria) [2].…”
Section: Introductionmentioning
confidence: 99%